A New Digital Method for Assessing the Diversity of Creator Identities in the Howard-Tilton Memorial Library Media Services DVD Collection. (3rd April 2019) - Tillay, Rachel; Chapman, CC
ABSTRACT: Popular discussions of representation within the media industry often focus on the sexual orientation, racial, or gender-identities of the production staff and performers. Although this gives a clearer picture of who is "allowed" to create media, it doesn't address a media item's accessibility to viewers postcreation. The collection development strategies of libraries and other cultural heritage institutions can strengthen or impede inclusion efforts. In order to analyze the collection of the Howard-Tilton Memorial Library, using #52FilmsByWomen as an inspiration, the authors created a customizable tool set and workflow which can be adapted to be used at other organizations.